NILAI-NILAI MORAL YANG TERCERMIN DALAM NOVEL SI ANAK PEMBERANI KARYA TERE LIYE - Eta Yulandari; Antonius Totok Priyadi; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research is focused on moral values which are reflected in the novel Si Anak Pemberani by Tere Liye. Theories used in this research were novel theory, moral values, and theory of literary learning implementation. The method in this research was descriptive, qualitative form, and sociology literature approach. Data in the form of sentences relating to the problem under research, namely moral values included moral values are reflected in the novel Si Anak Pemberani. The source of data in this research was the novel Si Anak Pemberani by Tere Liye. The technique used was documentary study technique. Data collection tool was the writer itself as the main instrument. The results of this study were: (1) Moral values seen from the relationship between humans and God included: (a) grateful for life, (b) worship. (2) Moral values seen from the relationship between humans and themselves included: (a) self-confidence, (b) responsibility, (c) self-extension, (d) honesty, (e) fear, (f) revenge,              (g) simplicity, (h) longing. (3) Moral values seen from the relationship between humans and others included (a) mutual help, (b) mutual cooperation,              (c) compassion (4) Moral values seen from the relationship between humans and nature included: (a) humans used the nature in good way, (b) responsibility for development, (c) how to love the preservation of the nature, (d) humans with friendly nature. Writer has designed a learning plan that used narrative texts in the literature learning in high school in accordance with Basic Competencies 3.9 and 4.9. Keywords: Moral Values, Novel, Si Anak Pemberani